(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The non-linear dynamical system subject to tuned excitation is consider, and studied . The system is represented by two degree of freedom differential equations of the system and absorber. The method of multiple scale is applied to solve the system up to 3rd order approximation. Effect of different parameters is studied numerically all resonance cases are studied numerically to obtain the worst case . Stability of the system is investigated using both phase plane and frequency response curves.